Sliding member

By providing a plurality of unit alloy parts in the sliding alloy part and controlling the existence ratio of the soft phase, the problem of difficult control of the structure and composition of the sliding alloy part in the prior art is solved, and the fatigue resistance and heat viscosity of the sliding member are improved.

CN119816675APending Publication Date: 2025-04-11DAIDO METAL IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202480003844.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-05
Filing Date
2024-03-28
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the prior art, it is difficult to strictly control the structure and composition of the alloy, resulting in difficulty in improving sliding characteristics such as fatigue resistance.

Method used

By providing a plurality of unit alloy portions in the sliding alloy portion, and controlling the existence ratio of the first soft phase and the second soft phase in the boundary region and the alloy parent phase region, a Cu-based alloy is formed to improve the sliding characteristics.

Benefits of technology

By controlling the structure and composition of the sliding alloy portion, especially in the boundary region and the alloy master phase region, fatigue resistance and heat adhesive resistance of the sliding member can be improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119816675A_ABST
    Figure CN119816675A_ABST
Patent Text Reader

Abstract

A sliding member (10) is provided with a base material (11) and a sliding alloy part (12) that is provided on the surface (13) of the base material (11) and is formed from a Cu-based alloy having Cu as the main component by means of an assembly of a plurality of unit alloy parts (12A-12E). The sliding alloy section (12) includes: a first soft phase (31) that is present in a boundary region (22) defined as a preset range with respect to the cell interface (21); and a second soft phase (32) that is present in a region other than the boundary region (22). When the total area ratio of the first soft phases (31) included per unit area is a first area ratio (S1) and the total area ratio of the second soft phases (32) included per unit area is a second area ratio (S2), S1 < S2 is satisfied.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application is based on Japanese Patent Application No. 2023-061455 filed on April 5, 2023, and the contents thereof are cited herein. Technical Field

[0003] The invention relates to a sliding member. Background Art

[0004] For example, a sliding member of an axial shape is provided with a sliding alloy portion that slides with a counterpart on the surface of a substrate. The sliding alloy portion is provided integrally with the substrate by installing other components such as laser welding or sputtering. In the case where the sliding alloy portion is formed by installing other components on the substrate, it is easy to ensure the desired sliding performance of the sliding alloy portion because the organization and composition of the alloy of the other components are easily controlled. On the other hand, in the case where the substrate and the sliding alloy portion are constituted by different components like this, it is not easy for the sliding alloy portion to ensure the desired sliding characteristics as the wear proceeds. In addition, in the case where the substrate and the sliding alloy portion are made into different components, the outer peripheral surface of the sliding member having the sliding alloy portion and the interface of the housing on which the sliding member is installed may slide. Therefore, it is considered to form the sliding alloy portion by welding on the surface of the substrate (reference patent document 1).

[0005] However, in the case of Patent Document 1, although it is disclosed that the sliding alloy portion is formed by welding, the structure and composition of the alloy of the sliding alloy portion are not strictly controlled. Therefore, it is difficult to strictly control the structure and composition of the alloy of the sliding alloy portion. As a result, the sliding alloy portion formed by welding as in Patent Document 1 has a problem that it is difficult to improve sliding characteristics such as fatigue resistance.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent document 1: U.S. patent application publication No. US2021 / 0010462. Summary of the invention

[0009] Problem that the invention aims to solve

[0010] Therefore, an object of the present invention is to provide a sliding member in which the structure and composition of a sliding alloy portion formed by welding are controlled to improve the sliding characteristics.

[0011] Solutions for solving problems

[0012] A sliding component of one embodiment has a substrate and a sliding alloy portion, wherein the sliding alloy portion is provided on the surface of the substrate and is formed by a Cu-based alloy having Cu as a main component through a collection of a plurality of unit alloy portions. The sliding alloy portion includes: a first soft phase existing in a boundary region, wherein the boundary region is defined as a range pre-set based on a unit interface of the unit alloy portion; and a second soft phase existing in a region of the unit alloy portion other than the boundary region. In the sliding alloy portion, when the ratio of the total area of ​​the first soft phase contained per unit area is set to a first area ratio S1, and the ratio of the total area of ​​the second soft phase contained per unit area is set to a second area ratio S2, S1<S2.

[0013] The sliding alloy portion formed by welding is formed by a collection of multiple unit alloy portions. The sliding component of this embodiment limits the existence ratio of the first soft phase existing in the boundary area defined as a range pre-set based on the unit interface as the interface of the unit alloy portion and the second soft phase existing in the area other than the boundary area. Moreover, the first soft phase existing in the boundary area is less than the second soft phase existing in the area other than this. As a result, the propagation of cracks in the sliding alloy portion is reduced, especially in the boundary area close to the interface of the unit alloy layer. Therefore, it is possible to achieve improvement in sliding characteristics such as fatigue resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a schematic diagram showing the structure of a sliding member according to one embodiment.

[0015] Figure 2 It is a schematic diagram showing the structure of a sliding member according to one embodiment.

[0016] Figure 3 1 is a schematic cross-sectional view showing a sliding member according to one embodiment.

[0017] Figure 4 For the general Figure 1 Schematic diagram of the enlarged IV section.

[0018] Figure 5 It is a schematic cross-sectional view showing an example of a sliding member to which one embodiment is applied.

[0019] Figure 6 Schematic diagram showing a welding device for manufacturing a sliding member according to an embodiment.

[0020] Figure 7 It is a schematic diagram showing evaluation of examples and comparative examples of a sliding member according to one embodiment.

[0021] Figure 8This is a schematic diagram showing conditions for a fatigue strength test of a sliding member according to one embodiment.

[0022] Fig. 9 This is a schematic diagram showing conditions for a hot-stiction test of a sliding member according to one embodiment.

[0023] Fig.10 This is a schematic diagram showing the conditions of a wear test of a sliding member according to one embodiment. DETAILED DESCRIPTION

[0024] Hereinafter, a sliding member according to one embodiment will be described based on the drawings.

[0025] like Figure 1 As shown, the sliding member 10 has a base material 11 and a sliding alloy portion 12. The base material 11 is formed of an Fe-based material such as steel. The sliding alloy portion 12 is provided on a surface 13 of the base material 11 by welding. The sliding alloy portion 12 is formed of a Cu-based alloy having Cu as a main component. The sliding alloy portion 12 is formed by a collection of a plurality of unit alloy portions 12A, 12B, 12C, 12D, and 12E. The sliding alloy portion 12 is formed by welding. Figure 2 As shown, the sliding alloy portion 12 is formed into unit alloy portions 12A to 12E as a unit in each welding operation. Then, the sliding alloy portion 12 is formed into unit alloy portions 12A to 12E in sequence by continuing the welding operation. The sliding alloy portion 12 is polished, cut, etc. to remove the side opposite to the base material 11 until, for example, Figure 1 The position of the line X shown. Therefore, Figure 3 As shown, the sliding member 12 has a sliding surface 14 formed on the surface on the side opposite to the base material 11 for sliding with a counterpart (not shown). Figure 1 In the case of the sliding alloy portion 12, for the sake of explanation, an example is shown in which the sliding alloy portion 12 is composed of five unit alloy portions 12A to 12E. However, this is an example, and the sliding alloy portion 12 can be composed of any number of unit alloy portions as long as there are two or more. In addition, an intermediate layer formed by, for example, Cu plating may be provided between the substrate 11 and the sliding alloy portion 12.

[0026] like Figure 1 and Figure 2 As shown, the sliding alloy portion 12 forms a unit interface 21 between the plurality of unit alloy portions 12A to 12E, i.e., at the boundary portion. Specifically, the boundary portion between the unit alloy portion 12A and the unit alloy portion 12B is the unit interface 21A. Similarly, the boundary portion between the unit alloy portion 12B and the unit alloy portion 12C is the unit interface 21B, the boundary portion between the unit alloy portion 12C and the unit alloy portion 12D is the unit interface 21C, and the boundary portion between the unit alloy portion 12D and the unit alloy portion 12E is the unit interface 21D.

[0027] The sliding alloy portion 12 is based on the unit interface 21. Figure 4 As shown, a boundary region 22 is provided in a predefined area. Figure 4 As an example, the boundary portion between the unit alloy portion 12C and the unit alloy portion 12D is mainly shown. The boundary region 22 is set to a fixed range on each side of the adjacent unit alloy portions 12A to 12E based on the unit interface 21. Figure 1 As shown, when there are a plurality of unit alloy portions 12A to 12E, the unit alloy portion 12C is the range from the unit interface 21B with the unit alloy portion 12B to the unit interface 21C with the unit alloy portion 12D. The distance from the unit interface 21B to the unit interface 21C is set as the distance L1. Similarly, the distance from the unit interface 21C to the unit interface 21D sandwiching the unit alloy portion 12D is set as the distance L2. These distances L1 and L2 correspond to the pitch of the weld that forms the sliding alloy portion 12.

[0028] like Figure 4 As shown, the boundary region 22 set at the unit interface 21C of the unit alloy portion 12C and the unit alloy portion 12D is a range of 5% of the distance L1 to the unit alloy portion 12C side based on the unit interface 21C, and a range of 5% of the distance L2 to the unit alloy portion 12D side. Moreover, the region other than the boundary region 22 in the unit alloy portion 12C is the alloy parent phase region 23. That is, in the case of the unit alloy portion 12C, the region other than the boundary region 22 formed in the unit alloy portion 12C based on the unit interface 21B and the boundary region 22 formed in the unit alloy portion 12C based on the unit interface 21C is the alloy parent phase region 23.

[0029] The sliding alloy portion 12 includes a soft phase. The soft phase is softer than the matrix phase of the Cu alloy constituting the sliding alloy portion 12. In the case of the present embodiment, the soft phase is, for example, Bi, a Bi alloy, etc. When a Bi alloy is used as the soft phase, the soft phase may also include Se, etc. The soft phase is finely dispersed in the sliding alloy portion 12. Among them, the soft phase existing in the boundary region 22 is set as the first soft phase 31. In addition, the soft phase existing in the alloy parent phase region 23 is set as the second soft phase 32. The composition of the first soft phase 31 and the second soft phase 32 is roughly the same, and can be classified according to whether the region where they exist is the boundary region 22 or the alloy parent phase region 23. In addition, for simplicity, Figure 4 Only a part of the first soft phase 31 and the second soft phase 32 is shown by way of example.

[0030] In the boundary region 22 of the sliding alloy portion 12, the ratio of the total area of ​​the first soft phase 31 contained per unit area in the preset observation range is set as the first area ratio S1. In addition, in the alloy parent phase region 23 of the sliding alloy portion 12, the ratio of the total area of ​​the second soft phase 32 contained per unit area in the preset observation range is set as the second area ratio S2. The observation range is preferably set to a range sufficient to include the first soft phase 31 or the second soft phase 32 in the range. The observation range can be set to, for example, a range of 300μm×400μm. At this time, the first area ratio S1 and the second area ratio S2 are S1<S2. That is, in the sliding alloy portion 12, the first soft phase 31 present in the boundary region 22 is less in total area than the second soft phase 32 present in the alloy parent phase region 23. When a soft phase is included in the matrix of the Cu alloy as in the sliding alloy portion 12, the boundary portion between the matrix and the soft phase is weaker in strength than the region of the matrix where the boundary portion is not formed. Therefore, the cracks generated in the sliding alloy portion 12 due to the load applied during sliding are easy to propagate along the boundary between the matrix and the soft phase. In the present embodiment, the first soft phase 31 contained in the boundary region 22 near the unit interface 21 of the unit alloy portion 12 is less than the second soft phase 32 contained in the alloy parent phase region 23 away from the unit interface 21. Therefore, especially in the boundary region 22, the propagation of cracks in the sliding alloy portion 12 is reduced. Therefore, the strength of the sliding alloy portion 12 is improved, and the improvement of sliding characteristics such as fatigue resistance can be achieved. In addition, the crystal grain size of the sliding alloy portion 12 is different in the boundary region 22 and the alloy parent phase region 23. Specifically, the crystal grain size of the matrix in the boundary region 22 is smaller than the crystal grain size of the alloy parent phase region 23, which is less than 1 / 10. Like this, the sliding alloy portion 12 realizes the refinement of the crystal grain size in the boundary region 22 compared to the alloy parent phase region 23.

[0031] The maximum outer diameter Da of the second soft phase 32 present in the alloy matrix region 23 is Da≤20μm. That is, the second soft phase 32 is refined to an outer diameter Da of less than 20μm. The outer diameter Da of the second soft phase 32 is measured by selecting a particle of the second soft phase 32 that is considered to be the largest by visual inspection from any observation section extracted from the sliding alloy portion 12. A circumscribed circumscribed circle is set for the particle of the extracted second soft phase 32 that is considered to be the largest. Then, the diameter of the circumscribed circle is set as the outer diameter Da. Since the outer diameter Da of the second soft phase 32 is less than 20μm, the second soft phase 32 is refined. As a result, even in the alloy matrix region 23, the propagation of cracks along the boundary between the matrix and the second soft phase 32 is reduced. Therefore, it is possible to achieve an improvement in sliding properties such as fatigue resistance. In addition, by miniaturizing the second soft phase 32, the dispersibility of the second soft phase 32 in the alloy matrix region 23 is improved. Therefore, the second soft phase 32 included in the alloy matrix region 23 of the sliding alloy portion 12 can be stably supplied to the sliding portion sliding with the counterpart (not shown). Therefore, sticking at the sliding portion sliding with the counterpart can be reduced.

[0032] The sliding alloy portion 12 may further include a third soft phase 33. The third soft phase 33 is preferably present in the boundary region 22 and is formed of a specific element different from the first soft phase 31. The third soft phase 33 further preferably includes one or more elements selected from Sn, Ni, and Al as specific elements. The total area ratio of the third soft phase 33 is greater in the boundary region 22 than in the alloy parent phase region 23. The specific element forming the third soft phase 33 strengthens the matrix in the sliding alloy portion 12 by solid solution. In addition, the specific element improves the strength of the Cu-based alloy in the sliding alloy portion 12 by forming an intermetallic compound, which contributes to the improvement of wear resistance. In addition to the first soft phase 31, the second soft phase 32 and the third soft phase 33, the sliding alloy portion 12 may also contain up to 6 mass% of Zn.

[0033] The sliding alloy portion 12 functions as a sliding layer of the sliding member 10. The sum T12 of the contents of the first soft phase 31 and the second soft phase 32 contained in the sliding alloy portion 12 is preferably 3 mass % to 15 mass % relative to the mass of the sliding alloy portion 12. The total content of the first soft phase 31 and the second soft phase 32 contained in the sliding alloy portion 12 is more preferably 5 to 12 mass %. In addition, the content of the third soft phase 33 contained in the sliding alloy portion 12 is preferably 5 to 15 mass % relative to the mass of the sliding alloy portion 12. The content of the third soft phase 33 contained in the sliding alloy portion 12 is further preferably 8 to 12 mass %. The second soft phase 32 is a soft phase that reduces the fixation at the sliding portion that slides with the counterpart (not shown) and contributes to the improvement of the hot seizure resistance of the sliding alloy portion 12. Therefore, by setting the total content of the first soft phase 31 and the second soft phase 32 to 3 mass % or more, the fatigue resistance of the sliding alloy portion 12 can be ensured and the hot seizure resistance can be improved.

[0034] In addition, the sum T12 of the contents of the first soft phase 31 and the second soft phase 32 is preferably set to 15% by mass or less. By setting the sum T12 of the contents of the first soft phase 31 and the second soft phase 32 to 15% by mass or less, the content of the second soft phase 32 contained in the alloy parent phase region 23 becomes appropriate. As a result, the propagation of cracks in the sliding alloy portion 12 can be suppressed with high accuracy. As a result, it is possible to achieve both further improvement of the fatigue resistance of the sliding alloy portion 12 and improvement of the hot seizure resistance of the sliding member 10 by reducing the propagation of cracks.

[0035] In addition, by setting the total content T3 of the third soft phase 33 to 5% by mass or more, the strength of the sliding member 10 at the sliding alloy portion 12 can be ensured. Furthermore, the content of the third soft phase 33 is preferably set to 15% by mass or less. In this way, by setting the content of the third soft phase 33 to 15% by mass or less, the Cu-based alloy forming the sliding alloy portion 12 will not be too hard, and the strength and toughness of the sliding alloy portion 12 can be achieved.

[0036] As described above, the sliding alloy portion 12 is formed by welding. Therefore, the unit interface 21 may have Figure 4 The cross section of the sliding alloy portion 12 in the thickness direction is formed into a curved shape as shown. In this cross section, the intersection of the unit interface 21 and the substrate 11 is set as the intersection point P, and the virtual tangent of the unit interface 21 at the intersection point P is set as the tangent line B. The angle A formed by the surface 13 as the interface between the sliding alloy portion 12 and the substrate 11 and the tangent line B is preferably 20°≤A≤70°. By setting the angle A to be less than 70°, the possibility of the crack propagating from the interface or sliding surface 14 between the substrate 11 and the sliding alloy portion 12 reaching the overlapping parts of the adjacent unit alloy portions 12A to 12E becomes higher. That is to say, in the case of Figure 4In the case of the unit interface 21C of the example, the crack propagated from the interface of the substrate 11 and the sliding alloy part 12 or the sliding surface 14 touches the overlapping unit interface 21 before propagating to the opposite side. Therefore, the propagation of the crack generated near the interface or the sliding surface 14 to the opposite side via the sliding alloy part 12 can be suppressed. In addition, by setting the angle A to be more than 20°, the alloy parent phase region 23 is easily exposed on the sliding surface 14 after the sliding alloy part 12 is formed. Since the alloy parent phase region 23 is a Cu-based alloy, it has high resistance to hot sticking. Therefore, it is possible to improve the resistance to hot sticking while ensuring the fatigue resistance of the sliding alloy part 12. In addition, when the cross-section of the unit interface 21 in the thickness direction of the sliding alloy part 12 is formed into a straight line, the angle A formed by the unit interface 21 and the above-mentioned surface 13 is preferably 20°≤A≤70°.

[0037] In order to improve the wear resistance, the sliding alloy portion 12 may also include hard particles added from the outside. When adding hard particles, the addition amount H of the hard particles is preferably 5% by mass or less, more preferably 2% by mass or less. The Vickers hardness HV of the sliding alloy portion 12 is preferably 80 to 120, more preferably 90 to 110. By setting the hardness HV of the sliding alloy portion 12 to 80 or more, the deformation of the sliding alloy portion 12 caused by the load brought by the unillustrated counterpart can be reduced. In addition, in order to reduce the influence on the counterpart, the hardness HV of the sliding alloy portion 12 is preferably 120 or less.

[0038] The sliding member 10 may be subjected to machining such as cutting and polishing, and then a covering layer, an intermediate layer, etc. may be provided on the surface of the sliding alloy portion 12 opposite to the substrate 11. Figure 5 As shown, the sliding member 10 can use a cylindrical or tubular shaft member 41 as a base material 11, and provide a sliding alloy portion 12 by welding on the outer periphery of the shaft member 41. Thus, the sliding member 10 can be used as a rotating shaft member that supports a planetary gear, for example.

[0039] Next, a method for manufacturing the sliding member 10 according to the present embodiment will be described.

[0040] like Figure 6 As shown, the sliding member 10 of this embodiment forms a sliding alloy portion 12 on a base material 11 by welding using laser cladding. When forming the sliding alloy portion 12, a laser 51 of a welding device 50 is irradiated on the base material 11. By irradiation with the laser 51, a powder 53 supplied to the base material 11 along with the irradiation with the laser 51 is melted. The molten powder 53 forms a molten pool 52, which solidifies by cooling, thereby forming the sliding alloy portion 12. For example, Figure 5As shown, when the shaft member 41 is used as the substrate 11, the shaft member 41 rotates around the axis when the laser 51 is irradiated. As a result, the sliding alloy portion 12 is continuously formed on the outer peripheral surface of the surface 13 of the shaft member 41. As an example, when the shaft member 41 with a diameter of 150 mm is used as the substrate 11, the rotation speed of the shaft member 41 is preferably set to 1πrad / min~5πrad / min. In addition, the rotation speed of the shaft member 41 is preferably set to 1.5πrad / min~4πrad / min. At the same time, the moving speed of the shaft member 41 in the axial direction is preferably set to 10mm / min~50mm / min. In this way, by rotating the shaft member 41 and moving in the axial direction, the sliding alloy portion 12 is formed in a roughly tight spiral shape on the surface 13 of the shaft member 41. As a result, the cross section of the formed sliding alloy portion 12 becomes a state where the unit alloy portions 12A~12E are gathered. In the case of this embodiment, the output power of the laser 51 is preferably 1kW~10kW. The melting amount of the powder 53 relative to the output of the laser 51 , that is, the specific melting amount, is preferably 0.3 kg / kW to 1 kW / kg. The specific melting amount can be calculated from the output of the laser 51 and the supply speed of the powder 53 .

[0041] As an example, the powder 53 of the Cu-based alloy as the sliding alloy portion 12 contains 5 mass% to 15 mass% of Sn, 3 mass% to 15 mass% of Bi, and the remainder is Cu and inevitable impurities. In addition, the composition of the powder 53 of the Cu-based alloy can be set according to the sliding alloy portion 12 to be formed. The sliding alloy portion 12 formed on the surface of the substrate 11 is preferably formed with a thickness of 2 mm or less. In addition, the formed sliding alloy portion 12 is more preferably formed into a thickness of 1 mm or less by mechanical processing such as cutting and polishing.

[0042] In the present embodiment, the sliding alloy portion 12 is formed by welding using laser cladding, and a unit interface 21 is formed at the boundary between the unit alloy portions 12A to 12E. Moreover, in the boundary region 22 including the unit interface 21, the matrix of the Cu-based alloy is refined, and the total area ratio occupied by the soft phase is relatively reduced. As a result, the propagation of cracks is prevented in the boundary region, and fatigue resistance is improved. In addition, the method of forming the sliding alloy portion 12 is not limited to the above-mentioned laser cladding.

[0043] Hereinafter, examples of the sliding member 10 according to the present embodiment will be described.

[0044] Three test pieces were prepared in each of the embodiments and comparative examples. Figure 7As shown, the area ratio S1, the area ratio S2, the maximum outer diameter Da of the second soft phase 32, the total content T12, the total content T3, and the angle A were calculated and measured. The area ratio S1, the area ratio S2, and the maximum outer diameter Da of the second soft phase 32 show the maximum values ​​among the measurement results measured by 3 test pieces. In addition, the angle A shows the average value of the measurement results measured by 3 test pieces. In addition, the examples and comparative examples evaluated the sliding characteristics by the following tests: "fatigue strength test" based on the maximum specific pressure P1 without fatigue, "hot sticking test" based on the maximum specific pressure P2 without hot sticking, and "wear test" based on the wear amount Z.

[0045] The observation of the sliding alloy portion 12 is carried out by cutting the sliding alloy portion 12 along a cross section perpendicular to the advancing direction of the welding by laser cladding. The cross section is etched after polishing. In addition, the unit interface 21, the boundary region 22 and the alloy parent phase region 23 are divided from the cross section. The soft phase contained in the boundary region 22 is the first soft phase 31, and the soft phase contained in the alloy parent phase region 23 is the second soft phase 32.

[0046] An observation range of 300 μm×400 μm is arbitrarily set from the divided boundary region 22, and the set observation range is magnified to 300 times by an optical microscope to observe the crystal grain size of the boundary region 22. The largest grain in the observation range of the boundary region 22 is extracted, and the diameter of the circumscribed circle of the extracted grain is measured as the first crystal grain size Dc1. In addition, in the case of the alloy matrix region 23, an observation range of 300 μm×400 μm is arbitrarily set from the divided alloy matrix region 23, and the set observation range is magnified to 100 times by an optical microscope to observe. The largest grain in the alloy matrix region 23 is extracted, and the diameter of the circumscribed circle of the extracted grain is measured as the second crystal grain size Dc2.

[0047] An arbitrary observation range of 300 μm×400 μm extracted from the boundary region 22 is magnified 500 times with an optical microscope, and the first area ratio S1 of the first soft phase 31 contained in the boundary region 22 is measured. Similarly, an arbitrary observation range of 300 μm×400 μm extracted from the alloy matrix region 23 is magnified 500 times with an optical microscope, and the second area ratio S2 of the second soft phase 32 contained in the alloy matrix region 23 is measured. These first area ratio S1 and second area ratio S2 can be mechanically measured, for example, by applying image processing to an image of the observation range, based on the difference in color tone of the matrix and the soft phase. However, in this case, the mechanical measurement conditions of the first area ratio S1 and the second area ratio S2 are set to be the same.

[0048] Regarding the alloy hardness, after polishing the cross section of the sliding alloy portion 12, the hardness HV of the sliding alloy portion 12 was measured using a Vickers hardness tester with a load of 5 N. Regarding the hardness HV, the test piece was measured three times and the average value was calculated. Figure 8 The conditions shown were for 1×10 7 Cycle. In the fatigue strength test, the set pressure ratio applied to the test piece is set to 100 MPa as the initial value, and the test is carried out by increasing the pressure ratio by 10 MPa each time. If no fatigue damage occurs in the test piece until the specified cycle is completed, the fatigue strength test for the set pressure ratio is recorded as passed. On the other hand, if fatigue damage occurs in the test piece before the specified cycle is completed, the set pressure ratio before the set pressure ratio is recorded as the maximum pressure ratio P1 without fatigue.

[0049] Hot tack test use Fig. 9 The conditions shown are as follows. In the hot-stick test, the specific pressure is increased by 5 MPa every 10 minutes to increase the maximum specific pressure without hot-sticking. In the hot-stick test, the test piece is measured 3 times, and the average value is calculated as the maximum specific pressure P1. The wear test uses Fig.10 The conditions shown in the figure were used. In the wear test, the start and stop were repeated in the form of 0.5 second acceleration, 1.0 second speed maintenance, 0.5 second deceleration, and 2.0 second stop. In the wear test, this series of start and stop was repeated for 20 hours, and the reduction in thickness of the sliding alloy portion 12 after the implementation was measured. In the wear test, the test piece was implemented 3 times, and the average value of these reductions was calculated as the wear amount Z.

[0050] exist Figure 7 In the examples and comparative examples shown, it is shown whether the sum T12 of the contents of the first soft phase 31 and the second soft phase 32 is within the range of 3 to 15 mass %. Examples and comparative examples in which the sum T12 is within the range of 3 to 15 mass % are indicated by "○". On the other hand, examples and comparative examples in which the sum T12 is not within the range of 3 to 15 mass % are indicated by "×". Specifically, the sum T12 of Example 5 is less than 3 mass %. In addition, the sum T12 of Example 6 is greater than 15 mass %. Similarly, it is shown whether the sum T3 of the contents of the third soft phase 33 is within the range of 5 to 15 mass %. Examples and comparative examples in which the sum T3 is within the range of 5 to 15 mass % are indicated by "○". On the other hand, examples and comparative examples in which the sum T3 is not within the range of 5 to 15 mass % are indicated by "×". Specifically, the sum T3 of Example 7 is less than 5 mass %. In addition, the sum T3 of Example 8 is greater than 15 mass %.

[0051] exist Figure 7In the examples and comparative examples shown, it is shown whether the addition amount H of hard particles is 5% by mass or less. Examples and comparative examples without the addition of hard particles are indicated by "-". Example 11 has an addition amount H of 2% by mass or less, indicated by "◎". Example 12 has an addition amount H of 5% by mass or less, indicated by "○". Example 13 has an addition amount H of more than 5% by mass, indicated by "×".

[0052] In the evaluation of the examples and comparative examples, the result that the maximum specific pressure P1 without fatigue in the fatigue resistance test was 120 MPa or more was evaluated as "○: Pass". Furthermore, the result that the maximum specific pressure P2 without heat seizure in the heat seizure test was 45 MPa or more, the wear amount Z in the wear test was 4 μm or less, and the maximum specific pressure P1 without fatigue was 140 MPa or more was evaluated as "◎: Excellent". On the other hand, the result that the maximum specific pressure P1 without fatigue was less than 120 was evaluated as "×: Fail".

[0053] like Figure 7 As shown, in Examples 1 to 13, the relationship between the first area ratio S1 and the second area ratio S2 is S1<S2. In contrast, in Comparative Example 1, the relationship between the first area ratio S1 and the second area ratio S2 is S1>S2. Examples 1 to 13 in which the relationship between the first area ratio S1 and the second area ratio S2 is S1>S2 are improved particularly in fatigue resistance compared to Comparative Example 1. In this way, in the example in which the first area ratio S1 of the boundary region 22 is reduced, fatigue resistance as a sliding characteristic can be improved.

[0054] In Examples 1 to 13, the maximum outer diameter Da, the sum T12, the sum T3, the angle A, and the addition amount H of the second soft phase 32 can be set to control the hot seizure resistance, fatigue resistance, and wear resistance. Therefore, after comprehensively considering the hot seizure resistance, fatigue resistance, and wear resistance, Examples 1 to 13 were judged as "◎: excellent" or "○: qualified". In contrast, the fatigue resistance of Comparative Example 1 was inferior to that of Examples 1 to 13 and was judged as "×: unqualified".

[0055] The present invention described above is not limited to the above-described embodiment, and can be applied to various embodiments without departing from the gist of the invention.

Claims

1. A sliding member comprising a substrate and a sliding alloy portion, The sliding alloy portion is provided on the surface of the substrate and is formed by a Cu-based alloy having Cu as a main component through the collection of a plurality of unit alloy portions. The sliding alloy portion comprises: A first soft phase exists in a boundary region, wherein the boundary region is defined as a range preset based on a unit interface of the unit alloy portion; and a second soft phase existing in a region other than the boundary region in the unit alloy portion, When the total area ratio of the first soft phase per unit area in a preset observation range is set as a first area ratio S1 and the total area ratio of the second soft phase per unit area in the observation range is set as a second area ratio S2, S1<S2. 2 . The sliding member according to claim 1 , further comprising a third soft phase, the third soft phase existing in the boundary region and originating from a specific element different from that of the first soft phase.

3. The sliding member according to claim 1, wherein: The maximum outer diameter Da of the second soft phase is 20 μm or less.

4. The sliding member according to claim 2, wherein: In the sliding alloy portion, a total T12 of contents of the first soft phase and the second soft phase is 3 to 15 mass %, and a total T3 of contents of the specific elements constituting the third soft phase is 5 to 15 mass %.

5. The sliding member according to claim 1, wherein: The cross section of the unit interface in the thickness direction is formed into a curved shape, When a virtual tangent line is defined for the unit interface at an intersection of the unit interface and the substrate, an angle A formed by an interface between the unit alloy portion and the substrate and the tangent line is 20°≤A≤70°.

6. The sliding member according to claim 2, wherein: The first soft phase and the second soft phase are Bi or a Bi alloy, The specific elements contained in the third soft phase are one or more elements selected from Sn, Ni, and Al.

7. The sliding member according to claim 1, wherein: The bearing alloy portion further includes hard particles in an addition amount H of 5 mass % or less.

8. The sliding member according to claim 1, wherein: The bearing alloy portion has a Vickers hardness HV of 80-120.

9. The sliding member according to claim 1, wherein: The substrate is a shaft member, and the bearing alloy layer is provided on an outer periphery of the shaft member.

Citation Information

Patent Citations

  • Reading device, reading method, program, and system

    JP2023061455A

  • Wind turbine gearbox and method for producing a wind turbine gearbox

    US20210010462A1